Skeleton key eaudiobook - Horowitz, Anthony (Alex Rider, 2003)
Alex Rider of Point Blank is back in another hair-raising adventure. Although the 14-year-old undercover agent has escaped great dangers and has twice saved the world, he now faces his most deadly adversary yet on a tropical island off the coast of Cuba. General Sarov was once an important leader in Communist Russia. Now in exile on Skeleton Key, he is full of bitterness for what his country has become. Sarov plans to put Russia in power again. And if the rest of the world won't agree with his demands, he will detonate a nuclear bomb. It's up to Alex to stop this deadly tyrant or die trying. Like a teenaged James Bond, Alex faces incredible foes and encounters spectacular adventures. Fast-moving and full of suspense, Skeleton Key will keep even the most reluctant reader glued to the headphones. "Fasten your seatbelts."—Kirkus Reviews